DOKTRIN ALLAH: PERSPEKTIF KRISTEN DAN IMPLIKASINYA DI ERA MODERN - Sarmauli Sarmauli; Adi Hardani, Rengga Kaharapen, Helnita, Yemima Nathalia (CV. ADIBA AISHA AMIRA, 2023)
The doctrine of God, as a core theological tenet in the Christian perspective, has undergone significant developments over time. This research aims to provide an in-depth analysis of the evolution of the doctrine of God and its implications in the context of the modern era. Utilizing both theological and social approaches, this study investigates how views on the character of God, salvation, and the relationship between humans and the divine have evolved over time. The doctrine of God not only serves as the foundation of Christian faith but also plays a crucial role in shaping ethical and moral perspectives within society. The implications of the doctrine of God in the social context illustrate how religious values influence human behavior in daily life. In an era filled with challenges and complexity, a profound understanding of the doctrine of God becomes essential in addressing existential questions and providing moral guidance. This study also highlights the dynamics of change in the understanding of the doctrine of God amidst contemporary Christian society. The central question of how theology adapts to social and technological changes is a focal point of this research. The results of this analysis offer new insights into the relevance of the doctrine of God in addressing contemporary issues such as advanced technology, religious pluralism, and pressing social concerns. This research is expected to contribute to a deeper understanding of how the doctrine of God in the Christian perspective not only endures in the modern era but also provides meaningful guidance for individuals and communities facing the challenges of the times.